THE INFLUENCE OF CUSTOMER RELATIONSHIP MARKETING, TRUST AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY OF CONVENTIONAL X BANK IN SIDOARJO - Musfiqoh; Dewi Komala Sari (International Journal of Business, Law and Political Science, 2025)
Objective: The purpose of this study was to determine the effect of Customer Relationship Marketing Trust, Customer Satisfaction, and Customer Loyalty on Conventional Bank Customer Loyalty in Sidoarjo. Method: The research approach in this study is quantitative research. The population includes all consumers who use Bank products and a sample size of 100 people. The type of data used is quantitative data using primary and secondary data sources. The data collection method in this study used a questionnaire. The analysis technique used is multiple linear regression analysis with the help of SPSS v.25 software. Result: The results prove that Customer Relationship Marketing affects the loyalty of Conventional Bank Customers in Sidoarjo. Trust affects the loyalty of Conventional Bank Customers in Sidoarjo. Satisfaction affects the loyalty of Conventional Bank Customers in Sidoarjo. Novelty: This study highlights the impact of Customer Relationship Marketing, Trust, and Satisfaction on the loyalty of Conventional Bank Customers in Sidoarjo.